THE DEGREE OF EXISTENCE OF GENDER STEREOTYPES IN THE PERSONALITY OF MODERN UZBEKS (NAMANGAN PROVINCE AS AN EXAMPLE): Личность, гендер, гендерный стереотип, андрогиния, узбеки. (Scientific journal of the Fergana State University, 2025)
It is known that the manifestation of gender stereotypes is influenced by socio-economic changes in global societies and is manifested differently in different cultures. Therefore, it is important to study the manifestation of gender stereotypes in personality traits in different cultures. In this article, we analyze a special study conducted to determine the level of manifestation of gender stereotypes in the personality of modern Uzbeks. S. Bem's questionnaire called “Sex Role Inventory (BSRI)” was used as a basis for the research. According to research, the concept of androgyny presented by S.Bem is studied and the degree of manifestation of gender stereotypes in the personality of modern Uzbeks is determined and analyzed.